Long‐term detection of clodronate in equine plasma by liquid chromatography–tandem mass spectrometry. Issue 8 (12th May 2021) - Garcia, Patrice; Perot, Isabelle; Loup, Benoit; Balssa, Frederic; Jaubert, Murielle; Delcourt, Vivian; Dujardin, Chris; Popot, Marie‐Agnes; Bailly‐Chouriberry, Ludovic
Abstract: Clodronate is a non‐nitrogen‐containing bisphosphonate drug approved in equine veterinary medicine. Clodronate is prohibited for use in competition horses; therefore, to set up an appropriate control, detection times and screening limits are required. The quantitative method in plasma consisted of addition of chloromethylene diphosphonic acid as internal standard. Automated sample preparation comprised a solid phase extraction with weak anion exchange properties on microplate. After methylation of the residue with trimethyl orthoacetate, analysis was conducted by high‐performance liquid chromatography–tandem mass spectrometry. Using a weighting factor of 1/(concentration) 2, good linearity was observed in the range of 1 to 500 ng/ml, with low limits of detection and quantification of 0.5 and 1 ng/ml, respectively. Precision and accuracy determined at four concentrations were satisfactory, with an error percentage less than 15%. Absence of carry‐over and good stability of clodronic acid in plasma after a long‐term storage at −20°C were verified. The method was successfully applied to the quantification of clodronic acid in plasma samples from horses administered with a single intramuscular administration of Osphos® at a mean dose of 1.43 ± 0.07 mg/kg. The observed detection time will be verified in a clinical population study conducted in diseased horses. Abstract : Clodronate is a non‐nitrogen‐containing bisphosphonate drug approved in equine veterinary medicine and prohibited for use in competition horses. A quantitative method in plasma was developed using WAX 96 well plate and methylation before analysis in LC‐MS/MS. In order to determine the detection time, the method has been applied on samples collected through to a PK study conducted on six healthy horses.